Are Sarcopenia and Myosteatosis in Elderly Patients with Pelvic Ring Injury Related to Mortality, Physical Functioning and Quality of Life? - Hester Banierink (MDPI AG, 2021)
The purpose of this study was to evaluate the prevalence of sarcopenia and/or myosteatosis in elderly patients with pelvic ring injuries and their influence on mortality, patient-perceived physical functioning and quality of life (QoL). A multicenter retrospective cohort study was conducted including elderly patients aged ≥ 65 treated for a pelvic ring injury. Cross-sectional computed tomography (CT) muscle measurements were obtained to determine the presence of sarcopenia and/or myosteatosis. Kaplan–Meier analysis was used for survival analysis, and Cox proportional hazards regression analysis was used to determine risk factors for mortality. Patient-reported outcome measures for physical functioning (SMFA) and QoL (EQ-5D) were used. Multivariable linear regression analyses were used to determine the effect of sarcopenia and myosteatosis on patient-perceived physical functioning and QoL. Data to determine sarcopenia and myosteatosis were available for 199 patients, with a mean follow-up of 2.4 ± 2.2 years: 66 patients (33%) were diagnosed with sarcopenia and 65 (32%) with myosteatosis, while 30 of them (15%) had both. Mortality rates in patients at 1 and 3 years without sarcopenia and myosteatosis were 13% and 21%, compared to 11% and 36% in patients with sarcopenia, 17% and 31% in patients with myosteatosis and 27% and 43% in patients with both. Higher age at the time of injury and a higher Charlson Comorbidity Index (CCI) were independent risk factors for mortality. Patient-reported mental and emotional problems were significantly increased in patients with sarcopenia.